2016
DOI: 10.1016/s1875-5372(16)30115-1
|View full text |Cite
|
Sign up to set email alerts
|

Hard Magnetization Direction and Its Relation with Permeability of Conventional Grain-oriented Electrical Steel

Abstract: Magnetic properties of conventional grain-oriented electrical steel sheets are different in various directions. In the present paper, Epstein standard samples were cut with different angles to rolling direction, and the corresponding magnetic properties of samples were tested. Results show that the hard magnetization direction to the rolling direction is around 60°. Conventional elliptical models are not accurate to simulate permeability at all magnetic intensities, and parabolic and hybrid models with high ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…For instance, Karatza et al reported a non-negligible hydrogen generation of 0.229 mg from water through a magnetic pre-poling (M = 48.3 mT) of the Fe 3 O 4 system [70]. The magnetic pre-poling was demonstrated to induce re-orientations of the magnetic poles of each grain making them behave like small magnets and results in the stabilization of the borders between grains [71]. Besides, the presence of both electric and magnetic properties in multiferroic materials permits the manipulation of the magnetism via electric fields and electricity via magnetic fields thanks to the magnetoelectric coupling [72].…”
Section: Theoretical Calculations 271 Electronic Propertiesmentioning
confidence: 99%
“…For instance, Karatza et al reported a non-negligible hydrogen generation of 0.229 mg from water through a magnetic pre-poling (M = 48.3 mT) of the Fe 3 O 4 system [70]. The magnetic pre-poling was demonstrated to induce re-orientations of the magnetic poles of each grain making them behave like small magnets and results in the stabilization of the borders between grains [71]. Besides, the presence of both electric and magnetic properties in multiferroic materials permits the manipulation of the magnetism via electric fields and electricity via magnetic fields thanks to the magnetoelectric coupling [72].…”
Section: Theoretical Calculations 271 Electronic Propertiesmentioning
confidence: 99%